P18.07 Hiv post-exposure prophylaxis in an australian regional centre: patient demographics and outcomes from 2011–2014. (13th September 2015) - Patruno, J; Yeganeh, S; Russell, D
Abstract : Introduction: Post-exposure prophylaxis (PEP) is a pharmacological method of preventing seroconversion following a high-risk exposure to human immunodeficiency virus (HIV). The Cairns Sexual Health Service is the central prescribing organisation for all occupational and non-occupational PEP presentations in the Cairns greater region. A retrospective analysis of presentations from 2011 to 2014 was performed to identify patterns of PEP use, re-presentation, follow-up and patient outcomes. Methods: Pharmacy records for all patients prescribed PEP at the Cairns Sexual Health Service from 01/01/2011 to 31/12/2014 were obtained. 121 presentations were identified of which 14 were excluded for incomplete patient details. A remaining 107 presentations for 81 clients were included for assessment. Charts for all 81 patients were audited with patient demographics, exposure type, follow-up attendance and outcome data collated. An excel format of the information was generated for analysis. Results: Non-occupational exposures accounted for 92% (n = 98) of presentations, whilst occupational exposures accounted for 8% (n = 9). 91% of presentations were males, 75% of which were men who have sex with men. Unprotected anal intercourse was responsible for 76% of non-occupational PEP. Re-presentations for PEP were high at 24%. Patient follow up was low with only 51% returning within 12 weeks of PEP completion, however, 13% were travellers who may have left the region. One patient who was lost to follow-up later underwent seroconversion to HIV. Two individuals with multiple presentations went on to access pre-exposure prophylaxis (PrEP). Conclusion: High rates of re-presentation and loss to follow-up indicate areas for improved response from our service. The rates of re-presentation reveal a need for further education and counselling of patients to reduce their exposure risks. At present there is no formal follow-up system at CSHS for patients prescribed PEP. Given the number of patients lost to follow-up an active system may be considered in the future. Disclosure of interest statement: No conflicts of interest to declare.